NAION AND ANTICOAGULANTS: BRIDGING THE GAP WITH RATIONALE-BASED THERAPY - Nusanti, Syntia; Rachman, Andhika; Marcia Budihardja, Brigitta; Ruth Eldinia, Lourisa; Delima Andini, Nadia; Kartasasmita, Arief; M., Sidik; Prayitnaningsih, Seskoati; Roswita Harahap, Alida; Kekalih, Aria; Darminto Gondhowiardjo, Tjahjono (Journal of Ayub Medical College Abbottabad, 2024)
Background: NAION, a multifactorial disorder with an unclear mechanism has limited insight on its treatment option. Despite conflicting results in its relation to hypercoagulation, many metabolic risk factors associated with NAION are intertwined with hypercoagulation. We aim to investigate the impact of anticoagulant therapy in the vascular and visual function of NAION patients. Methods: A prospective interventional study was conducted in the Neuro-Ophthalmology Division, Department of Ophthalmology at FKUI-RSCM Kirana from October 2020 to April 2022, involving two groups of NAION subjects: hypercoagulation and non-hypercoagulation. All subjects received 80 mg of aspirin daily, with the hypercoagulation group additionally receiving 2 mg of warfarin. We assessed capillary perfusion (CP) and flux index (FI) using OCTA, along with changes in visual acuity (Snellen chart test) and visual field (Humphrey Visual Field - HVF) at presentation and one month after treatment. Results: The hypercoagulation group had 14 subjects, while the non-hypercoagulation group had 7. This research found a significant decrease for CP (p=0.003) and FI (p=0.001) in both groups. CP and FI in all quadrants decreased more in the non-hypercoagulable group without anticoagulant therapy, although the difference between the two groups was not significant (p=0.198 for CP and p=0.243 for FI). Hypercoagulation group showed significant visual field improvements (p=0.033 for MD and p=0.014 for VFI). Most subjects within hypercoagulation showed improvement although not all of it was significant, while the majority of the non-hypercoagulation group showed no changes.